Challenges And Obstacles Faced By English Teachers With Limited Technology Skills In Using Technology For Teaching (A Case of Study at SMPN 1 Wonggeduku) - M. Fadli (Journal of Innovative and Creativity, 2025)
The development of information and communication technology has brought great changes in the world of education, including in the process of learning English. Amidst the rapid development and importance of technology and digital literacy in education, there are still many challenges and obstacles experienced by English teachers who have limited technological skills, especially in the process of integrating technology into learning at SMPN 1 Wonggeduku. These problems are not only related to low technical competence, but also limited supporting facilities, lack of continuous training, and psychological constraints such as lack of self-confidence. Therefore, this study aims to find out more about the challenges and constraints experienced by English teachers who have limited technological skills. This research uses a qualitative approach with a case study design, with data collection through interviews, observation, and documentation involving two English teachers. In addition, the subjects of this study were English teachers at SMPN 1 Wonggeduku, totaling 2 people. Then, the data in this study were analyzed through three stages, namely data reduction, data display, and conclusion drawing. The results show that the main obstacles lie in the basic skills of using digital devices, such as laptops and projectors, as well as difficulties in operating learning applications. In addition, the limited internet network, the lack of supporting devices in each class, and the unavailability of technology experts also exacerbate the problem.